Schottky contact characteristics of various metals at different temperatures - Ganesan Krishnan, 1986-; Zulkafli Othaman,lcsupervisor (2009)
Project Paper (Sarjana Muda Sains (Fizik)) - Universiti Teknologi Malaysia, 2009